Monetarism & supply side economics [free market thought in the late 20th century]. - Klamer, Arjo.; Reynolds, Alan.; Rukeyser, Louis (Nashville, TN : Knowledge Products, 1988)
Discusses the opinion of Milton Friedman that markets are efficient if government does not exercise discretionary power over the nation's money supply. Reviews Robert Mundell's viewpoint of supply-side economics based on incentives for individual workers and investors, as they advocate measures (such as lower tax rates) to improve economic performance.
LC copy lacks guide.
Scripts by Arjo Klamer and Alan Reynolds; narrated by Louis Rukeyser.
Keywords: Friedman, Milton, -- 1912-2006.; Mundell, Robert A; Economics; Supply-side economics; Chicago school of economics